Pengaruh Kompetensi, Independesi, Tekanan Waktu, Pengalaman, Dan Etika Auditor Terhadap Kualitas Audit( Studi pada Kantor Akuntan Publik di Jawa Tengah ) - Adinoto, Nugroho; , Eny Kusumawati, SE, MM,AK,CA (2016)
This study quantitative study that is specific to evaluate the relationship of competence, independence, time budged pressure, experience, and ethical of auditors to audit quality. This study was conducted by distribusing questionnaries to KAP in Central java. Sample in this study was 45 respondents from 8 KAP. Sampling technique this study using convenience sampling method. The hypothesis test using multiple linear regression with SPSS version 20. All variabel in this study were measured using Likert Scale.The results showed that all independent variables have an effect on audit quality. The test result obtained R2 values of 0,826 which means 82,6% of variables that effect the audit quality could be explained by the independent variables in this study, while the remaining 17,4% is explained by variables outside the model. T test result showed that all independent variables have on effect on audit quality.